miR-15b-5p Promotes Growth and Metastasis in Breast Cancer by Targeting HPSE2 - Wu, Balu; Liu, Guohong; Jin, Yanxia; Yang, Tian; Zhang, Dongdong; Ding, Lu; Zhou, Fuling; Pan, Yunbao; Wei, Yongchang (Frontiers in Oncology, 2020)
MicroRNAs (miRNAs) can participate in many behaviors of various tumors. Prior studies have reported that miR-15b-5p in different tumors can either promote or inhibit tumor progression. In breast cancer, the role of miR-15b-5p is unclear. The main objective of this paper is to explore miR-15b-5p effects and their mechanisms in breast cancer using both in vitro and in vivo experiments. This study showed that miR-15b-5p expression was upregulated in breast cancer compared with normal breast tissue and was positively correlated with poor overall survival in patients. Knockdown of miR-15b-5p in MCF-7 and MD-MBA-231 breast cancer cells restrained cell growth and invasiveness and induced apoptosis, whereas overexpression of miR-15b-5p achieved the opposite effects. We next revealed a negative correlation between miR-15b-5p and heparanase-2 (HPSE2) expression in breast cancer. Knockdown of miR-15b-5p significantly increased HPSE2 expression at both mRNA and protein levels in breast cancer cells in vitro. The underlying mechanisms of miR-15-5p in breast cancer were investigated using luciferase activity reporter assay and rescue experiments. In addition, miR-15b-5p knockdown significantly inhibited tumor growth in a xenograft model in mice. In summary, we showed that miR-15b-5p promotes breast cancer cell proliferation, migration, and invasion by directly targeting HPSE2. Accordingly, miR-15b-5p may serve both as a tool for prognosis and as a target for therapy of breast cancer patients.